On the Forensic Characterization of the Identity of the Subjects of Crimes in the Field of High Technologies - ISSATAYEVA, Baglan T.; BEGALIEV, Ernar N.; JILKISHIYEV, Ruslan B.; RAIMZHAN, Serik B. (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
The relevance of the study is due to the fact that timely prevention of negative manifestations of cybercrime, and even more so the identification of the perpetrators, is one of the main and most important tasks of law enforcement services of all civilized states, since measures to prevent, detect, uncover and investigate such crimes cannot be effective only at the national level because of the transnational and transbondary nature of the Internet. The article reveals the possibilities of applying the features of the blockchain technology in the investigation of criminal cases. A possible mockup of an electronic criminal case using blockchain technology has been compiled. Methods for digitization of criminal cases investigation are proposed, as well as the possibility of using the non-traditional branch of the forensic technology (psycho-physiological portrait).